Konsep dan Metode Pendidikan Anak Menurut Pemikiran Syekh Nawawi Al-Bantani - Rohmani, Mahfud Salimi (Prodi Pendidikan Agama Islam STIT Al-Khairiyah Cilegon, 2017)
Considering the importance of a child's education, today's parents rarely apply education according to the concepts and methods of the Nawawi Sheikh among them; If a 10-year-old is asked to pray then the child should be beaten 10 times in a harmless part of the body, most parents now allow their child even if they do not pray, the majority of their parents do not teach that way, even though it is contrary to the concept of Sheikh Nawawi Al- Help me. Child education concept according to Sheikh Nawawi Al-Bantani: Nomination, selection of spouse or spouse, pre-birth education, post-birth education. Method of education of children according to Sheikh Nawawi Al-bantani: When the child reaches the age of 6, provide the education of manner. Age is 9 and the child should move his / her own bed to sleep on his own; She is 16 and the child is married.